Compilation theory of Malay aesthetics: concepts of Malay beauty in arts / Nurkhazilah Idris...[et.al] - Idris, Nurkhazilah; Omar Basaree, Ruzaika; Mohd Radzi, Fazlina; Mohd Yussof, Fatrisha; Zahari, Farihan; Dasuki, Shaliza (2016)
This research is compilation theory of Malay aesthetics point up from several scholars which is AI Ghazali, Abdullah Mohamed (Nakula), Sulaiman Esa, Syed Ahamad Jamal, Ruzaika Omar Basaree and Zakaria Ali. This research is looking at the theory Malay aesthetics which the beauty Concept of art and it is hoped that this research would reach out to the public and further provide a bridge linking the public's understanding with matters related to the visual arts, enlightening the theory of Malay aesthetic principles along with greater appreciation on Malay element of meanings behind philosophers effort and thus encourage public appreciation and understanding on the concept of beauty within the Malay ideology context on visual arts. Findings from this research are hoped to be as significant contribution to the Malaysian Art history and as part of Malay Muslim ideologies.